Comparative pathologic analysis of mediastinal B-cell lymphomas: selective expression of p63 but no GATA3 optimally differentiates primary mediastinal large B-cell lymphoma from classic Hodgkin lymphoma - Hyun-Jung Kim; Hee Kyung Kim; Gyeongsin Park; Soo Kee Min; Hee Jeong Cha; Hyekyung Lee; Suk Jin Choi; Hee Young Na; Ji-Young Choe; Ji Eun Kim (Diagnostic Pathology, 2019)
Abstract Background Interpretation of mediastinal biopsy is often challenging even for experienced pathologists especially when a hematolymphoid neoplasm is suspected. Primary mediastinal large B-cell lymphoma (PMLBCL) and classic Hodgkin lymphoma (CHL) represent two major types of mature B-cell lymphomas of the mediastinum. Although PMLBCL and mediastinal CHL share many clinicopathologic characteristics, their treatment strategies and responses are remarkably different. We therefore aimed to find distinctive histologic or protein markers to better differentiate these two lesions. Methods Search for primary mediastinal B-cell lymphomas found 52 consecutive cases from 3 university hospitals of Korea during 2005 to 2012. Among them, 32 cases that were available for additional immunohistochemistry (IHC) assessment were enrolled in this study. These cases consisted of the following: CHL (N = 13), PMLBCL (N = 16), and B-cell lymphoma unclassifiable, with features intermediate between diffuse large B-cell lymphoma and CHL (gray zone lymphoma, N = 3). Along with the clinicopathologic findings, the expression of p63, GATA3 and cyclin E was investigated by IHC in the three categorized lesions mentioned above. Results Most clinical features overlapped between PMLBCL and CHL except for the increased disease progression and mortality found in PMLBCL. In the pathologic review, the presence of epithelioid granuloma favored a diagnosis of CHL, whereas reticulated or alveolar patterns of fibrosis were characteristic of PMLBCL. For protein markers, p63 was predominantly positive in PMLBCL (15/16) compared with CHL (2/13), which indicates that p63 is a marker of the highest diagnostic accuracy when calculated by the area under the ROC curve. GATA3 was expressed in the majority of CHL cases (10/13) compared with PMLBCL (0/16), while the expression of cyclin E was only rarely present in a minor population of PMLBCL. Conclusions P63 expression in tumor cells, even focal expression, and no GATA3 is the most helpful feature in distinguishing PMLBCL from mediastinal CHL.